Cost‐effectiveness of levofloxacin prophylaxis against bacterial infection in pediatric patients with acute myeloid leukemia. Issue 10 (25th July 2020) - McCormick, Meghan; Friehling, Erika; Kalpatthi, Ramasubramanian; Siripong, Nalyn; Smith, Kenneth
Abstract: Background: Infections are the leading cause of therapy‐related mortality in pediatric patients with acute myeloid leukemia (AML). Although effectiveness of levofloxacin antibacterial prophylaxis in oncology patients is recognized, its cost‐effectiveness is unknown. This study evaluated epidemiologic data regarding levofloxacin use and the cost‐effectiveness of this strategy as the cost per bacteremia episode, intensive care unit (ICU) admission, and death avoided in children with AML. Procedure: A retrospective cohort study using the Pediatric Health Information System (PHIS) database compared demographic and clinical characteristics and receipt of levofloxacin prophylaxis in children with AML admitted for chemotherapy from January 1, 2014, through December 31, 2018. We then developed a decision analysis model in this population that compared costs associated with bacteremia, ICU admission, or death secondary to bacteremia to levofloxacin prophylaxis cost from a healthcare perspective. Time horizon is one chemotherapy cycle. Probabilistic and one‐way sensitivity analyses evaluated model uncertainty. Results: Prophylaxis cost $8491 per bacteremia episode prevented compared with an average added hospital cost of $119 478. Prophylaxis cost $81 609 per ICU admission avoided, compared with an average added hospital cost of $94 181. Prophylaxis cost $220 457 per death avoided. In sensitivity analysis, at a willingness‐to‐pay threshold of $100 000 per bacteremia episode avoided, prophylaxis remained cost‐effective in 94.6% of simulations. Prophylaxis use was more common in recent years in patients with relapsed disease and with chemotherapy regimens considered more intensive. Conclusion: Prophylaxis is cost‐effective in preventing bacterial infections in patients with AML. Findings support increased use in patients considered at high risk of bacterial infection secondary to myelosuppression.